2017 International Conference on Rehabilitation Robotics (ICORR) 2017
DOI: 10.1109/icorr.2017.8009401
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive learning to speed-up control of prosthetic hands: A few things everybody should know

Abstract: Abstract-A number of studies have proposed to use domain adaptation to reduce the training efforts needed to control an upper-limb prosthesis exploiting pre-trained models from prior subjects. These studies generally reported impressive reductions in the required number of training samples to achieve a certain level of accuracy for intact subjects. We further investigate two popular methods in this field to verify whether this result equally applies to amputees. Our findings show instead that this improvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
1
13
1
Order By: Relevance
“…To overcome distribution mismatches, transfer learning and domain adaptation approaches have been used in several domains, including computer vision (Saenko et al, 2010 ; Tommasi et al, 2010 ), and natural language processing (Ben-David et al, 2010 ; Daumé et al, 2010 ). In myoelectric control, several studies explored the use of previous models from different subjects to reduce the amount of required training data (Farina et al, 2002 ; Tommasi et al, 2013 ; Patricia et al, 2014 ), but performance increase was not confirmed after proper model optimization (Gregori et al, 2017 ). The fact that the motor modules are common to the subjects can provide physiological foundations to include within the prosthesis a subject-independent motor memory.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome distribution mismatches, transfer learning and domain adaptation approaches have been used in several domains, including computer vision (Saenko et al, 2010 ; Tommasi et al, 2010 ), and natural language processing (Ben-David et al, 2010 ; Daumé et al, 2010 ). In myoelectric control, several studies explored the use of previous models from different subjects to reduce the amount of required training data (Farina et al, 2002 ; Tommasi et al, 2013 ; Patricia et al, 2014 ), but performance increase was not confirmed after proper model optimization (Gregori et al, 2017 ). The fact that the motor modules are common to the subjects can provide physiological foundations to include within the prosthesis a subject-independent motor memory.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental setup is based on the "realistic setting" proposed in a previous work [32]. The setting was considered as "realistic" as it exploits real data coming from the Ninapro Dataset, recorded during the execution of daily life gestures.…”
Section: Methodsmentioning
confidence: 99%
“…The standardized data were used according to the protocol already proposed for control by Englehart and Hudgins [7], where features were extracted from a sliding window of 200 ms and an increment of 10 ms. As described in the papers presenting the datasets, sEMG signals were filtered from 50 Hz (and harmonics) power-line interference using a Hampel filter [31,36]. The resulting set of windows was subsequently split in the training set and test set as inputs for the classifier [32]. The sEMG representation used in this setting was the average of the marginal discrete wavelet transform (mDWT), mean absolute value (MAV) and variance (VAR) features [37].…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Similar techniques have been used for the classification of electromyography (EMG) signals (Gregori et al, 2017; Tommasi et al, 2013). The benefit of such techniques in the control of prosthetic devices is, however, debated (Gregori et al, 2017) and may need to be further developed. A similar problem is being studied in robotics for training visual recognition systems from small dataset (Pasquale et al, 2016; Schwarz et al, 2015).…”
Section: Neuroengineering Meets Aimentioning
confidence: 99%